Refusal Strategies Performed by Speakers of Different Ages - Citra Kinanti Kayang (Lexicon, 2014)
This pragmatic research was conducted to identify and classify the refusal strategies performed by two groups of speakers of different ages. It was also conducted to investigate the differences and similarities in the strategies. The first group consisted of 20 speakers aged 17-27 years old and the second group consisted of 20 speakers aged 40-50 years old. There were 240 refusals performed as the data of this research which were classified according to the classification proposed by Felix-Bradesfer (2008). This research foundthat there were 9 direct refusals, 45 indirect refusals, and 66 adjuncts to refusals performed by the younger speakers. There were 7 direct refusals, 49 indirect refusals, and 64 adjuncts to refusals that were performed by the older speakers. This research also found that there were more similarities than differences on the refusal performed by the two groups.